2016
DOI: 10.2196/jmir.4124
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Internet Use by Informal Caregivers of Children and Adolescents: An Integrative Literature Review

Abstract: Background Internet-based health resources can support informal caregivers who are caring for children or adolescents with health care needs. However, few studies discriminate informal caregivers’ needs from those of their care recipients or those of people caring for adults. Objective This study reviews the literature of health-related Internet use among informal caregivers of children and adolescents. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 43 publications
(179 reference statements)
5
40
1
Order By: Relevance
“…Multimedia approaches including internet and web-based programs are a means for providing informational support to caregivers; they also found that effective parent education through communication technologies can augment the mental well-being of children [95]. Our results are consistent with earlier reports in this field that suggest that web-based interventions are effective for caregivers managing mental health issues in adolescents [91,96,97].…”
Section: Principal Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Multimedia approaches including internet and web-based programs are a means for providing informational support to caregivers; they also found that effective parent education through communication technologies can augment the mental well-being of children [95]. Our results are consistent with earlier reports in this field that suggest that web-based interventions are effective for caregivers managing mental health issues in adolescents [91,96,97].…”
Section: Principal Findingssupporting
confidence: 90%
“…Identifying appropriate communication technologies to inform and support caregivers may be a challenge, but it is essential to understand their adoption thereof [87,88]. Information dissemination delivered through communication technologies is gradually replacing traditional approaches [89], but the implementation in health care [90] and among caregivers [14,91] is still lacking. Communication technologies can distribute an unprecedented amount of information through technology such as electronic devices, system software, and information networks such as the internet, which provides access to resources [92,93].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Despite efforts of the multidisciplinary healthcare team to provide excellent discharge education prior to the child going home, caregivers may encounter disorganized care, poor communication, and information mismanagement, especially when transitioning from the hospital to home (Mitchell et al, 2013). Park, Kim, and Steinhoff (2016) found that the majority of informal caregivers of children with medical issues were the parents. The minority of informal caregivers are other relatives or legal guardians.…”
Section: Introductionmentioning
confidence: 99%
“…Young adults seem to perform more health searches on the Internet [3,[7][8][9]12,13] due to their higher digital skills [14]. More educated users use the Internet more in regard to health [7,9,12,13,15,16], as do people with higher incomes [13,17,18]. Geographically, according to some authors, users who live in urban areas perform more health searches on the Internet [11], while others point out that this would be the case for those who live further away from medical services [15].…”
Section: Introductionmentioning
confidence: 99%